How Does Intolerance of Uncertainty Predict Work Readiness? Unveiling the Role of Self-efficacy - Salsabilla, Miranda Putri; Ulya, Laila Listiana (Universitas Ahmad Dahlan, 2025)
As students transition into the workforce, work readiness becomes essential—particularly for those entering high-uncertainty environments such as startups. While prior studies have established the negative impact of intolerance of uncertainty (IU) on various career-related outcomes, the underlying mechanisms by which IU affects work readiness (WR) remain insufficiently explored. Specifically, little is known about the mediating role of self-efficacy (SE) in this relationship, particularly within the context of internship experiences. Furthermore, existing research has rarely focused on student populations engaged in real-world transitions, such as internships in startup environments characterized by volatility and ambiguity. Addressing this gap, the present study investigates the effect of IU on WR with SE as a mediator. Data were collected through an online survey involving 208 student interns participating in the Certified Internship and Independent Study Program (MSIB), selected via purposive sampling. Validated Indonesian versions of the Intolerance of Uncertainty Scale-12 (IUS-12), General Self-Efficacy Scale (GSES), and Work Readiness Scale (WRS) were utilized. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The results indicate a significant indirect effect of IU on WR through SE, whereas the direct effect of IU on WR was not statistically significant. These findings underscore the critical role of self-efficacy in enhancing students’ work readiness and mitigating the negative impact of uncertainty.